Resilience, transition or transformation? A comparative analysis of changing water governance systems in four southern cities. (April 2014) - Hordijk, Michaela; Sara, Liliana Miranda; Sutherland, Catherine
Delegating state responsibilities for the management of water resources to regional bodies and the provision of drinking water and sanitation to local governments has led to new configurations in urban water governance. Drawing on case studies from four cities in the global South (Guarulhos, Arequipa, Lima and Durban), this article analyzes recent changes in these configurations, with particular attention to the role and power of the municipality in this process. This paper explores to what extent these new configurations reveal a move towards resilience, transition or even transformation. It concludes that there are clear indications of transition in all cases, and in Guarulhos and Durban even some signs of transformation. Given that transformative changes in the legal and institutional framework, and even in values and attitudes, have not yet affected the existing power structures, the question is to what extent these signs of transformation will reach their full potential.